The novel ATR inhibitor VE-821 increases sensitivity of pancreatic cancer cells to radiation and chemotherapy - Prevo, Remko; Fokas, Emmanouil; Reaper, Philip M.; Charlton, Peter A.; Pollard, John R.; McKenna, W. Gillies; Muschel, Ruth J.; Brunner, Thomas B. (Cancer biology & therapy, 2012)
DNA damaging agents such as radiotherapy and gemcitabine are frequently used for the treatment of pancreatic cancer. However, these treatments typically provide only modest benefit. Improving the low survival rate for pancreatic cancer patients therefore remains a major challenge in oncology. Inhibition of the key DNA damage response kinase ATR has been suggested as an attractive approach for sensitization of tumor cells to DNA damaging agents, but specific ATR inhibitors have remained elusive. Here we investigated the sensitization potential of the first highly selective and potent ATR inhibitor, VE-821, in vitro. VE-821 inhibited radiation- and gemcitabine-induced phosphorylation of Chk1, confirming inhibition of ATR signaling. Consistently, VE-821 significantly enhanced the sensitivity of PSN-1, MiaPaCa-2 and primary PancM pancreatic cancer cells to radiation and gemcitabine under both normoxic and hypoxic conditions. ATR inhibition by VE-821 led to inhibition of radiation-induced G 2 /M arrest in cancer cells. Reduced cancer cell radiosurvival following treatment with VE-821 was also accompanied by increased DNA damage and inhibition of homologous recombination repair, as evidenced by persistence of γH2AX and 53BP1 foci and inhibition of Rad51 foci, respectively. These findings support ATR inhibition as a novel approach to improve the efficacy and therapeutic index of standard cancer treatments across a large proportion of pancreatic cancer patients.